Management and outcomes in pregnant patients with monogenic diabetes due to pathogenic variants in GCK and HNF1A genes - Szopa, Magdalena; Zawadzka, Karolina; Kania, Michał; Witek, Przemysław; Cyganek, Katarzyna (Frontiers in Endocrinology, 2025)
BackgroundWhile treatment algorithms for the most common forms of monogenic diabetes (MD) are well established, managing affected pregnancies remains a clinical challenge. This study aimed to evaluate the clinical management and pregnancy outcomes in patients with the two prevalent MD subtypes: GCK and HNF1A.MethodsWe analyzed 36 pregnancies from 27 patients: 18 pregnancies occurred in the context of 14 patients with GCK-hyperglycemia, and 18 pregnancies in 13 patients with HNF1A-MD. Patients’ characteristics, mode of treatment, glycemic control assessed by HbA1c, glycemia and pregnancy outcomes were evaluated.ResultsThe mean age of participants was 31.64 ± 3.91 years, similar between groups. Time from the diagnosis of diabetes was longer in subtypes HNF1A-MD (8.00 ± 6.20 vs. 3.46 ± 4.05 years, p=0.046). Preconception BMI and HbA1c were similar between groups. HbA1c during pregnancy was within recommended limits but significantly lower in the HNF1A group during the second trimester (33.2 ± 6.0 vs 38.0 ± 6 mmol/mol, p=0.032). Mean fasting glucose was higher in the GCK-hyperglycemia group in the first trimester (5.6 ± 0.8 vs. 4.9 ± 1.4 mmol/l, p=0.044). Before pregnancy diet therapy predominated in GCK-hyperglycemia (56.0% vs 0%, p<0.001), while insulin therapy was more frequent in HNF1A-MD (67.0% vs. 17.0%, p=0.006). All patients were switched to insulin therapy during pregnancy. Incidences of miscarriages were limited to 2 cases in HNF1A-MD; 1 case of prolonged neonatal hypoglycemia occurred in GCK-hyperglycemia. Maternal and neonatal outcomes were generally favorable.ConclusionsPregnancy outcomes in patients with subtypes of monogenic diabetes: GCK-hyperglycemia and HNF1A were comparable and generally favorable. Individualized insulin therapy, regular monitoring and structured outpatient care support safe management even without fetal genotyping, though universal insulin in GCK subtypes diverges from emerging genotype-based practice.